Enhancing EFL Students’ Speaking Skills Through Digital Storytelling - Hepnyi Samosir (Universitas Muhammadiyah Tangerang, 2026)
This classroom action research aims to investigate the effectiveness of digital storytelling in improving English speaking skills. The study was carried out at Universitas Prabumuih, involving 21 students from the Diploma 3 Accounting Computerization Study Program, Faculty of Computer Science. The study was conducted in two cycles, following the stages of planning, action, observation, and reflection. Data were gathered through speaking tests, observations, student reflections, and researcher journals. The results demonstrated a consistent improvement in students’ performance. The mean score increased from 64.48 in the pre-test to 69.88 in cycle I, and further 76.55 in Cycle II. Moreover, the percentage of students who met the minimum criterion score of 75 as outlined at the outset of the study, increased from 0% in the pre-test to 80.95% by the end of Cycle II. Qualitative data revealed some challenges students encountered during the learning process in Cycle I, including technical barriers, low self-confidence, linguistic limitation, and incomplete tasks due to time management. To address these challenges, the learning process in Cycle II was modified by providing enhanced literary support, script templates, and modules, as well as timely and respectful feedback. In conclusion, the integration of digital storytelling in teaching speaking has proven to be an effective strategy for enhancing students’ speaking abilities.